2022
DOI: 10.21203/rs.3.rs-1857423/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the gut microflora of common kestrel (Falco tinnunculus) according to differences in sex, age, and physiological condition

Abstract: Background Gut microbes play an important role in animal health, and their compositions and changes can reflect the physical condition of animals. However, the gut microbes of most birds, especially raptors, have been poorly investigated. This study used 16S rRNA gene sequencing technology to determine the gut microbiome of rescued common kestrels, compared the composition and diversity of the gut microbiome of common kestrels under different physiological conditions, and analyzed the effects of sex and age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Nevertheless, our findings align with a handful of existing studies, which show that Firmicutes, Proteobacteria, and Actinobacteriota (Fig. 1A) are among the most abundant bacterial phyla in raptor gut microbiota [73,80,107,121]. Notably, while studies focusing on raptors lack descriptions of the eukaryotic microbiota, our results are in accordance with research conducted in other bird species that also revealed that the two major fungal phyla, Ascomycota and Basidiomycota, are predominant in the gut microbiota [68,116,119].…”
Section: Gut Microbiota Profilesupporting
confidence: 92%
“…Nevertheless, our findings align with a handful of existing studies, which show that Firmicutes, Proteobacteria, and Actinobacteriota (Fig. 1A) are among the most abundant bacterial phyla in raptor gut microbiota [73,80,107,121]. Notably, while studies focusing on raptors lack descriptions of the eukaryotic microbiota, our results are in accordance with research conducted in other bird species that also revealed that the two major fungal phyla, Ascomycota and Basidiomycota, are predominant in the gut microbiota [68,116,119].…”
Section: Gut Microbiota Profilesupporting
confidence: 92%